Meta-Analysis of the Intervention Effects of PERMA Model-Based Nursing Care on Breast Cancer Patients - Yiran Liu; Yancan Wang; Wei Su; Yangyang Sun; Lin Cheng (International Journal of Biology and Life Sciences, 2026)
Objective: Systematically evaluate the intervention effect of nursing based on PERMA mode on breast cancer patients, and provide evidence-based evidence for tumor psychological nursing. Methods: Computer searches were conducted to retrieve randomized controlled trials (RCTs) from databases such as PubMed, Cochrane Library, Web of Science, CINAHL, Embase, China Biomedical Literature Database, CNKI, Wanfang, and VIP (up to March 2025), and data was analyzed using Review Manager 5.4. A total of 7 studies (672 patients) were included. Software: A total of 7 studies (672 patients) were included. The meta-analysis results showed that compared with the control group, this nursing model can reduce patients' anxiety (SMD=-2.58), depression (SMD=-3.79), fear of disease progression (MD=-5.70), fatigue (SMD=-8.16), and improve their sense of happiness (SMD=1.63) and psychological capital (MD=17.12), all of which have statistical significance (P